Expression of T cell receptor-alpha and -beta subunits in human thymocytes. An immunocytologic study. - Maggiano, N; Larocca, L; Piantelli, M; Acuto, O; Musiani, P (1987)
The expression of the T cell receptor (Ti)-alpha and -beta subunits in human thymocytes was studied with the use of two rabbit antisera directed at constant regions of human Ti-alpha- and Ti-beta-chains (H36 and H38, respectively). Immunoperoxidase techniques were employed to count by light and electron microscopy the cells, in the various thymocyte subsets, bearing Ti-alpha and Ti-beta subunits. Of the unfractionated thymocytes, 88% +/- 5 SD and 56% +/- 8 SD were labeled by H38 and H36, respectively. More than 90% of cells in cluster of differentiation (CD)-1+ (mainly cortical) and CD1-CD3+ (mainly medullary) subsets were stained with H38. When tested by H36, 51% +/- 6 SD of CD1+ and 81% +/- 8 SD of CD1-CD3+ thymocytes were positive. In the immature CD3-CD1- subpopulation, less than 3% of cells reacted with H36, whereas 15% +/- 3 SD were stained by H38. Flow cytometry revealed that CD1+ (mainly cortical) thymocytes expressed CD3 surface antigen in a percentage similar to that of CD1+ cells positive for Ti-alpha subunits. Indirect double labeling procedures with immunogold- and peroxidase-conjugated second antibodies demonstrated that almost all CD1+/Ti-alpha + cells expressed the surface CD3 antigen, whereas a large proportion of CD1+/Ti-beta + cells did not. These results indicate a sequential expression of Ti-beta and Ti-alpha subunits during intrathymic T cell differentiation. They also suggest that assembly and surface expression of the CD3-Ti complex are linked to the production of Ti-alpha-chains in addition to Ti-beta subunits. Last, the expression of Ti-alpha and Ti-beta subunits was studied in peanut agglutinin (PNA)+, CD1+ blasts representing the main, spontaneously proliferating intrathymic pool. The lack of Ti-alpha and Ti-beta subunits and the absence of surface CD3 antigen on most of these blasts suggest that immature T cells are compelled to proliferate in the thymus in a CD3-Ti complex independent manner.